2012
DOI: 10.1371/journal.pone.0036814
|View full text |Cite
|
Sign up to set email alerts
|

An Abundant Tissue Macrophage Population in the Adult Murine Heart with a Distinct Alternatively-Activated Macrophage Profile

Abstract: Cardiac tissue macrophages (cTMs) are a previously uncharacterised cell type that we have identified and characterise here as an abundant GFP+ population within the adult Cx3cr1GFP/+ knock-in mouse heart. They comprise the predominant myeloid cell population in the myocardium, and are found throughout myocardial interstitial spaces interacting directly with capillary endothelial cells and cardiomyocytes. Flow cytometry-based immunophenotyping shows that cTMs exhibit canonical macrophage markers. Gene expressio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

13
295
1
3

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 276 publications
(312 citation statements)
references
References 56 publications
13
295
1
3
Order By: Relevance
“…A large resident macrophage population has previously been described in the adult mouse heart (9,20). Here, we extend these observations and underscore the emerging concept that distinct macrophage lineages exist within tissues and have different biological roles in maintaining homeostasis, consistent with Ilya Metchnikoff's empirically derived concept of "physiologic inflammation" originally proposed in 1901 (21).…”
Section: Inhibition Of Monocyte Recruitment Preserves Embryonic-derivedsupporting
confidence: 84%
“…A large resident macrophage population has previously been described in the adult mouse heart (9,20). Here, we extend these observations and underscore the emerging concept that distinct macrophage lineages exist within tissues and have different biological roles in maintaining homeostasis, consistent with Ilya Metchnikoff's empirically derived concept of "physiologic inflammation" originally proposed in 1901 (21).…”
Section: Inhibition Of Monocyte Recruitment Preserves Embryonic-derivedsupporting
confidence: 84%
“…There is evidence that tissue homeostasis is subject to regulation by tissue resident MP, and that multiple modes of communication exist between parenchymal cells and resident MP (64,81,82,146,181,191). In the heart, for example, resident macrophages express high levels of HO-1 and CD163 and directly interact with endothelial cells and cardiac myocytes (134). Tissue-resident MP may integrate signals from the surrounding tissue as part of a global network (37,98).…”
Section: The Mononuclear Phagocyte Systemmentioning
confidence: 99%
“…myocardial | aging | T cells | inflammation | inflammaging T he myocardial cellular composition has been revisited in recent years, and leukocyte subsets residing in the healthy heart have been described (1)(2)(3)(4)(5)(6)(7)(8)(9)(10). Cardiac-resident macrophages exhibiting an M2-like gene expression profile were found to be distributed in close association with the coronary vascular bed (3), and niches for dendritic cells (CD11c + MHC-II high CD80/86 low ) were found near the cardiac valves of the intact heart (1).…”
mentioning
confidence: 99%
“…Cardiac-resident macrophages exhibiting an M2-like gene expression profile were found to be distributed in close association with the coronary vascular bed (3), and niches for dendritic cells (CD11c + MHC-II high CD80/86 low ) were found near the cardiac valves of the intact heart (1). It was also demonstrated that cardiac-resident MHCII + cells process and present myosin heavy chain-alpha-derived peptides under steady-state conditions (11,12) and prime T cells ex vivo (1).…”
mentioning
confidence: 99%